Efficacy and Safety of Transcatheter Mitral Valve Edge-to-Edge Repair with a MitraClip Device in Real-World Canadian Practice - Shamir R. Mehta, MD, MSc; Anita Asgar, MD; Robert Boone, MD; Josep Rodes-Cabau, MD, PhD; Eric A. Cohen, MD; Andrew Czarnecki, MD; Marino Labinaz, MD; Shahar Lavi, MD; Nicolo Piazza, MD; Kevin R. Bainey, MD; Akshay Bagai, MD; Jean-Michel Paradis, MD; et al. (CJC Open)
Background: Mitral transcatheter edge-to-edge repair (M-TEER) is a treatment option for patients with symptomatic mitral regurgitation (MR). The real-world experience with M-TEER in Canada has not been reported previously. Methods: We conducted an observational study of 1191 patients from 11 Canadian centres undergoing M-TEER with a MitraClip device (Abbott, location). M-TEER databases from each centre were collected centrally and merged into a single Canada-wide database. The primary outcome was MR severity before M-TEER vs at up to 1 year after M-TEER. Secondary outcomes included hospitalizations for heart failure (HF) and New York Heart Association (NYHA) functional class. Results: MR etiology was degenerative in 41%, and functional in 59%. The mean age was 76 years, and 36% were women. The proportion with MR ≥ 3+ was 97.3% before vs 11.0% at up to 1 year after M-TEER (absolute risk difference [ARD] 86.4%, P < 0.001). Hospitalization for HF occurred in 50.7% before vs 10.3% at up to 1 year after M-TEER (ARD 40.4%, P < 0.001), with similar benefit in patients with functional (ARD 44.8%, 95% confidence interval 39.5-50.1) and degenerative (ARD 34.8%, 95% confidence interval 29.0-40.6) MR. NYHA class III-IV HF was present in 82.8% before vs in 16.6% at up to 1 year after M-TEER (ARD 66.2%, P < 0.001). Single-leaflet detachment (1.0%) and mitral valve surgery (2.2%) were infrequent. Mortality was 1.3% in-hospital, and 12.7% at 1 year. Conclusions: In this first national registry of patients undergoing M-TEER in Canada, M-TEER resulted in a sustained reduction in MR and was associated with reduced HF hospitalizations and improvement in NYHA functional class, with a high degree of safety. This benefit was consistent in patients with functional and degenerative MR. Résumé: Contexte: La réparation transcathéter bord à bord de la valve mitrale (mitral transcatheter edge-to-edge repair ou M-TEER) est une option de traitement offerte aux patients qui présentent une régurgitation mitrale (RM) symptomatique. L’expérience avec la M-TEER dans la pratique réelle au Canada n’a jamais fait l’objet d’une étude auparavant. Méthodologie: Nous avons mené une étude observationnelle auprès de 1 191 patients se prêtant à une M-TEER avec MitraClip dans 11 centres canadiens. Les bases de données sur la M-TEER de chaque centre ont été rassemblées et fusionnées en une seule à l’échelle du Canada. Le paramètre d’évaluation principal consistait à comparer la gravité de la RM avant la M-TEER et jusqu’à 1 an après la M-TEER. Les paramètres d’évaluation secondaires comprenaient l’hospitalisation pour une insuffisance cardiaque et la classe fonctionnelle de la New York Heart Association (NYHA). Résultats: L’étiologie de la RM était dégénérative chez 41 % des participants et fonctionnelle chez les 59 % restants. L’âge moyen des participants était de 76 ans, et 36 % étaient des femmes. Le pourcentage de participants présentant une RM ≥ 3+ était de 97,3 % avant la M-TEER et de 11,0 % jusqu’à 1 an après la M-TEER (différence de risque absolu [DRA] : 86,4 %; p < 0,001); 50,7 % des patients ont été hospitalisés pour une insuffisance cardiaque avant la M-TEER, comparativement à 10,3 % jusqu’à 1 an après la M-TEER (DRA : 40,4 %; p < 0,001). Le bienfait a été similaire chez les patients présentant une RM fonctionnelle (DRA : 44,8 %; intervalle de confiance [IC] à 95 % : 39,5 à 50,1) et chez ceux présentant une RM dégénérative (DRA : 34,8 %; IC à 95 % : 29,0 à 40,6). Une insuffisance cardiaque de classe III-IV selon la NYHA était présente chez 82,8 % des patients avant la M-TEER et chez 16,6 % des patients jusqu’à 1 an après la M-TEER (DRA : 66,2 %; p < 0,001). Le décollement d’un seul feuillet (1,0 %) et la chirurgie de la valve mitrale (2,2 %) ont été peu fréquents. La mortalité a été de 1,3 % pendant l’hospitalisation et de 12,7 % à 1 an. Conclusions: D’après ce premier registre national canadien sur la M-TEER, cette dernière a entraîné une réduction durable de la RM. Elle a également été associée à une réduction des hospitalisations pour insuffisance cardiaque et à une amélioration de la classe fonctionnelle de la NYHA, parallèlement à un degré élevé d’innocuité. Ce bienfait a été uniforme chez les patients atteints de RM fonctionnelle et dégénérative.